2021
DOI: 10.1002/hed.26811
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of functional outcomes following surgical treatment of early tongue cancer

Abstract: Background Speech and swallowing are important outcomes following resection in early tongue cancers. Aim This prospective study was performed to compare speech, swallowing, and tongue mobility between secondary intention healing (SH) and primary closure (PC) in glossectomy for early tongue cancers. Methods Forty T1/T2 tongue cancers underwent wide excision followed by either PC or SH. Operative time, tube feeding, complications, speech, and swallowing were assessed in both groups at 1, 6, 12, and 24 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The flap harvesting was performed as described in previous reports [20] (Figure 1). a vital role in speech articulation, taste and protection of the upper airways [4,5]. Reconstructing the human tongue is a challenging endeavor due to its highly dynamic muscular structure, which cannot be precisely replicated using any existing technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flap harvesting was performed as described in previous reports [20] (Figure 1). a vital role in speech articulation, taste and protection of the upper airways [4,5]. Reconstructing the human tongue is a challenging endeavor due to its highly dynamic muscular structure, which cannot be precisely replicated using any existing technique.…”
Section: Methodsmentioning
confidence: 99%
“…The tongue is a crucial structure in the oral phase of swallowing, and is responsible for propelling food into the pharyngeal phase. It also plays a vital role in speech articulation, taste and protection of the upper airways [ 4 , 5 ]. Reconstructing the human tongue is a challenging endeavor due to its highly dynamic muscular structure, which cannot be precisely replicated using any existing technique.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, secondary intention is the simplest of all techniques. In a prospective study of 40 early tongue cancers, Pai et al [4 ▪▪ ] found that secondary intention healing resulted in improved mobility and articulation whereas outcomes were comparable to primary closure in terms of operative time, bleeding, duration of tube feeding, and pain. The authors’ results highlight the need for caution with primary closure to prevent mobility restriction.…”
Section: Primary and Secondary Intentionmentioning
confidence: 99%
“…8,9 However, this procedure imposes significant physical and psychological burdens on patients, including extensive trauma, altered appearance, impaired chewing, swallowing, and speech functions. 10 As a result, the treatment outcomes and 5 year overall survival rates remain unsatisfactory. 11 Consequently, there is a pressing need for diagnosis and precise image-guided surgery (IGS) or innovative noninvasive treatment methods that can effectively cure oral cancer, extend survival rates, and simultaneously maximize the preservation of patients' appearance and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Tongue cancer and floor of mouth cancer are both common types oral cancers. , Due to the intricate anatomy and close proximity to critical structures like major blood vessels, nerves, and the pharynx, oral cancer continues to challenge clinical treatment . Currently, the frontline approaches for oral cancer management involve a combination of surgery with preoperative/postoperative radiation therapy and immunotherapy. , Metastasis often leads to the failure of treatment in cancer patients, surgery typically entails extensive resection of the primary carcinoma and the sentinel lymph nodes (SLNs) to ensure complete removal of affected tissues. , However, this procedure imposes significant physical and psychological burdens on patients, including extensive trauma, altered appearance, impaired chewing, swallowing, and speech functions . As a result, the treatment outcomes and 5 year overall survival rates remain unsatisfactory .…”
Section: Introductionmentioning
confidence: 99%